Mechanism and Potential Therapy in Ameloblastoma: Akt Signaling Pathway - Steward Hadi; Leo Alberto Porjo; Ferry Sandra (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Ameloblastoma is the most common benign aggressive tumor. They are more prevalent in the mandible than in the maxilla, mostly observed on the posterior of the jaw. Ameloblastoma can arise at any age, however it most usually affect patients between the ages of 20 and 40. Numerous efforts have been made to develop molecular targeted therapies to treat cancers, such as Akt inhibitors. However, these drugs have not been tested for treating ameloblastoma yet, since underlying molecular factors have yet to be identified. This study was carried out to delineate possible molecular mechanisms related to the Akt signaling pathway in ameloblastoma and potential drugs for ameloblastoma treatment. CONTENT: Akt signaling pathway in ameloblastoma has been implicated in the formation and progression of tumors. Akt signaling is involved in various cellular mechanisms, such as cell cycle, apoptosis, and cytoskeletal rearrangement, which includes Phosphatidyl Inositol 3 Kinase (PI3K)-Akt signaling, Akt-Nuclear Factor (NF)-κB signaling, Akt-Mammalian Target of Rapamycin (mTOR) signaling, Akt-B-cell Lymphoma (Bcl)-2 Family signaling, Akt-Survivin signaling. Potential ways of treatments using chemical compounds and micro RNA (miRNA), and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) were explored as well.SUMMARY: The present review highlights various Akt signaling involved in ameloblastoma and its potential pathways for treatments, while the gold standard of ameloblastoma treatment is still surgery to remove the tumor, there are many potential agents through various means of inhibition for ameloblastoma. Therefore, understanding the underlying signaling on ameloblastoma is necessary to induce inhibition on ameloblastoma. More research in potential ways to inhibit Akt signaling in ameloblastoma will lead to a better management of ameloblastoma in the future. KEYWORDS: ameloblastoma, Akt, PI3K, NFkB, mTOR, Bcl-2, miRNA, CRISPR